The development of a research department in the French Swimming Federation: a paradigm evolution - Hellard, P. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The French national swimming team won 66 Olympic and World medals from 1998 to 2013, although it had won only 12 between 1984 and 1998. The growth of the French Swimming Federation's research department since 1998 has been one of the factors contributing to this success. The development of this department was a complex undertaking for many reasons. First, French swimming coaches and technical staff have not been trained within a scientific culture. Yet the coaches and staff possess extraordinarily diverse skills that in many ways depend on their personalities, personal histories, cultural background and past training experiences. This diversity highlights the need for widely differentiated and individualised scientific support. Second, the department's activity is expected to cover the broad range of issues related to training and high-level performance. This has required a multidisciplinary approach and the development of a wellfunctioning collaborative network. Last, as part of our mandate, the research department is called on to communicate and share our findings with all French territories. The first objective of the department is to formalise the most effective training practices through an analysis of coaching practices. The second objective is to build knowledge that is relevant to all issues touching on performance and health, such as motor learning, nutrition, the mobilisation of energy resources, altitude training, biomechanics and any other area related to high-level training. As a third objective toward performance optimisation, the department of research has for the past 15 years been piloting the development of technological processes to evaluate performance. This aspect of our activity has resulted in the development of high-tech tools and research equipment that have been meticulously constructed and shown to be well adapted to use in the field. In these three areas, the analysis of the most effective practices, knowledge building to enhance training, and the development of technologies for practitioners, the research department of the French Swimming Federation has been a leader in developing ideas, innovations and skills over the last 15 years.